Predictors and prevalence of postconcussion depression symptoms in collegiate athletes - Vargas, G.; Rabinowitz, A.; Meyer, J.; Arnett, P. A. (Journal of Athletic Training, 2015)
Context: Depression is common after concussion and is associated with functional outcome and quality of life after injury. However, few baseline predictors of postconcussion depressive symptoms (PCDS) have been found.